E-Comic Media in Enhancing Reading Literacy Among II Grade Elementary School Students - Chindytia; Raviza Magfira; Ni Putu Vina Widiantari (Indonesian Gender and Society Journal, 2025)
Reading literacy is an important competency for primary school students, but many low-grade students still experience difficulties. This study aims to test the effectiveness of e-comic media in improving reading literacy of grade II students using the Research and Development method with the ADDIE model. Participants consisted of 15 students selected by purposive sampling. Data were collected through interviews, literacy tests (pretest and posttest), and student response questionnaires. The data was then analyzed qualitatively and quantitatively.The results showed a significant increase from an average score of 73.3 to 88 with an N-Gain value of 0.55 (medium category). A total of 96% of students gave a positive response to the e-comic, stating that this media is interesting and helps understanding. Material, media, and language expert validation showed high feasibility with percentages of 85%, 92.5%, and 91.25%, respectively. This finding is in line with Piaget's theory that children aged 7-11 years need visual media. The conclusion of the study proves that e-comic is effective in improving reading literacy. The implication is that this media can be adopted as an innovative solution for literacy learning in the lower grades.